Monitoring the reactive oxygen species in spermatozoa during liquid storage of boar semen and its correlation with sperm motility, free thiol content and seasonality. (6th September 2021) - Khoi, Hoang Xuan; Shimizu, Kenji; Yoneda, Yoshitaka; Minagawa, Itaru; Abe, Yasuyuki; Kuwabara, Yasushi; Sasanami, Tomohiro; Kohsaka, Tetsuya
Abstract: Oxidative stress is an important factor affecting the quality of spermatozoa during liquid storage of boar semen; however, monitoring of reactive oxygen species (ROS) that provides direct insight into the oxidative status is not yet attempted. This study aimed to monitor ROS in boar sperm during liquid semen storage to determine its correlation with sperm motility and free thiol (SH) content, and seasonality. Ejaculate was collected from mature Duroc boars in a commercial farm in autumn and spring, diluted in Mulberry III extender, stored at 15°C, and examined daily for sperm ROS level, SH content and motility. The ROS levels in spermatozoa prepared during autumn and spring were constantly low until days 4 and 5 of storage, respectively, which thereafter progressively increased in association with the loss of sperm motility. The increased sperm ROS level correlated with the higher SH level and lower motility, which was accentuated from day 4 of storage and was higher in September, or early autumn. This study indicates that increased sperm ROS levels during liquid storage results in oxidative damage, causing loss of sperm motility, presumably through decreased sperm viability, suggesting that sperm ROS monitoring effectively evaluates the quality of boar semen.